Entrepreneurship in the long-run: Empirical evidence and historical mechanisms - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
We review and discuss research on the development of regional entrepreneurship over time. A particular focus is on the long-term persistence of regional levels of entrepreneurship, its explanation, and its meaning for economic development. What is the state of empirical research in this field, and what can explain the empirical findings? How are long-term trends of entrepreneurial activity linked to regional performance in terms of employment, gross domestic product (GDP), and innovative activity? Based on our assessments we derive conclusions for theory, policy implications, and avenues for further research.
Keywords: L26; M13; O1; O33; R11; 330; Entrepreneurship; self-employment; regional growth; entrepreneurialculture; historical analysis